Substitution or Complementarity? Sukuk–Bank Performance Resilience in Indonesia’s Dual Banking System - Nofrianto, Nofrianto; Zaenal, Muhammad Hasbi; Khairunnisa, Dini Anggreini; Sali, Najeeb Razul A (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This study examines whether sukuk serves as a substitute or complement to banks, offering new insights into the resilience and vulnerability of Indonesia’s dual banking system under macroeconomic shocks. Research Objectives: To examine the evolving sukuk–bank performance relationship before and after the 2020 global recession, and its implications for financial stability. Research Methods: Quarterly data (2015–2023) from 6 Islamic and 15 conventional banks are analyzed using a dynamic panel System GMM model to address endogeneity and bank-specific heterogeneity. Empirical Results: Prior to the crisis, the development of the sukuk market significantly reduced the profitability of Islamic banks, indicating a substitution effect. After the crisis, the negative impact on Islamic banks weakened, suggesting partial complementarity. Inflation widened margins, money supply reduced them, and GDP growth benefited only conventional banks. Implications: Aligning sukuk market growth with banking strategies can strengthen resilience, enhance competitiveness, and support stability in dual banking systems. JEL Classification: G21, G23, E44, E52 How to Cite:Nofrianto., Zaenal, M. H., Khairunnisa, D. A., & Sali, N. R. A. (2025). Substitution or Complementarity? Sukuk-Bank Performance Resilience in Indonesia’s Dual Banking System. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 563-xx. https://doi.org/10.15408/sjie.v14i2.46415.